Methodological issues in natural disaster loss normalisation studies. (15th March 2021) - Botzen, W.J. Wouter; Estrada, Francisco; Tol, Richard S.J.
ABSTRACT: The mixed results in Pielke (2020 ) for natural disaster loss normalisation studies are due to methodological differences. Flaws exist in commonly used normalisation approaches that assume unitary elasticities between exposure indicators and losses. We refute Pielke's arguments that statistical studies estimating these relationships are biased. We conclude with an agenda for future research.